Korban kekerasan dalam pacaran yang sulit meninggalkan hubungannya - Ifthiharfi, Ratu; Rizkyanti, Charyna Ayu; Akhyar, Muhammad (Jurnal Psikologi Sosial, 2024)
Dating violence (KDP) is one of the most prevalent cases in Indonesia. Most victims of the cases choose to stay in the relationship and forgive their partners. This study aims to investigate whether emotional regulation strategies mediate the role of romantic attachment components on affective and cognitive empathy toward victims of dating violence. Participants in the study were victims of dating violence aged 18-29 years (N= 367) who live in Java Island. Research samples were collected using volunteer techniques (opt-in) panels where participants agreed to be involved through an invitation on a website page without being formally recruited. This study employs The Basic Empathy Scale to measure the dimensions of empathy, the Experiences in Close Relationships Inventory to measure the type of romantic attachment components, and finally Emotion Regulation Questionnaire to measure the type of emotional regulation strategies. By model 4 of Hayes's analyses, the results showed that the reappraisal strategies type mediated the role of avoidance attachment toward empathy, both affective and cognitive. As practical implications, counselors are expected to establish secure attachments, particularly with their clients who experience dating violence in order to stabilize cognitive and affective empathy so they are able to live free of violent relationships.